Agar from Gracilaria gracilis (Gracilariales, Rhodophyta) of the Patagonic coast of Argentina-Content, structure and physical properties - Rodríguez, María Cecilia (2009)
Milled summer thalli of Gracilaria gracilis from Argentina were sequentially extracted with water at room temperature (RTW1-3), 70 C (W701-3) and 90 C (W901-2). Both W701 and W901 consisted of high molecular weight polysaccharides (ca. 540,000 Da), but polydispersity was higher for the major product W701 (yield, 72% of the recovered). Structural analyzes by methylation and 13C NMR spectroscopy revealed that W701 was mainly agarose. Alkaline treatment, together with structural analyzes, indicated a negligible proportion of precursor L-galactose 6-sulfate residues in this product, while they were clearly detected in the 13C NMR spectra of RTW2-3. The presence of floridean starch in W901 had an antagonistic effect on its gel strength, which resulted nearly three times lower than that of fraction W701. Ultrastructural observation by transmission electron microscopy showed that, after extraction with hot water, a partial loss of cell wall stratification and disorganization of the cuticle had occurred. Final cellular debris exhibited swelling in the microfibrillar component. After this first thorough study of the chemical composition and physical properties of the products of G. gracilis from Bahía Bustamante we conclude that a good quality agarose is obtained in high yield after extraction with water at 70 C without the requirement of alkaline pretreatment, which usually produces degradation of the polysaccharide.